1997
DOI: 10.1017/s0963180100007933
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control for Hospitals' Clinical Ethics Services: Proposed Standards

Abstract: Hospital ethics committees have become widespread over the last 25 years, stimulated by the Quinlan decision of the New Jersey Supreme Court, the report of a President's Commission, and most recently by the Joint Commission on Accreditation of Health Care Organizations (JCAHO), which now man dates that each hospital seeking accreditation have a functioning process for the consideration of ethical issues in patient care. Laws and regulations in several states require that hospitals establish ethics committees, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Desired personal attributes included tolerance, patience, compassion, honesty, self-knowledge, courage, prudence, humility, and integrity [70,[78][79][80]. Professional proficiencies sought after included prior training and experience with CEC practices [7,16,79,[81][82][83][84][85][86], ethico-legal knowledge [69, 78-81, 83, 86-96] and active involvement in promoting awareness of ethical issues in the clinical environment [80,91,92]. An effective CEC consultant also showed interest in organizational ethics [7], educating and guiding others on ethical issues [80,91,92] and aligning expectations and practice with institutional and CEC standards [82,86].…”
Section: Domains Assessedmentioning
confidence: 99%
“…Desired personal attributes included tolerance, patience, compassion, honesty, self-knowledge, courage, prudence, humility, and integrity [70,[78][79][80]. Professional proficiencies sought after included prior training and experience with CEC practices [7,16,79,[81][82][83][84][85][86], ethico-legal knowledge [69, 78-81, 83, 86-96] and active involvement in promoting awareness of ethical issues in the clinical environment [80,91,92]. An effective CEC consultant also showed interest in organizational ethics [7], educating and guiding others on ethical issues [80,91,92] and aligning expectations and practice with institutional and CEC standards [82,86].…”
Section: Domains Assessedmentioning
confidence: 99%
“…Provided that CECs work to such principles and their members are trained to do so then there is every reason to believe they can make an extremely positive contribution to improving clinical practice and the general quality of health care. 39 At their best, research ethics committees have made just such a contribution to good research practice in clinical medicine. Resistance to the creation of CECs risks, therefore, the appearance of self serving.…”
Section: Resultsmentioning
confidence: 99%
“…Strategic plans generate the direction for the daily activities of a particular service or agency 18 and like mission statements provide a guide for measuring accountability. 17 Given that six sites in this study do not have written strategic plans with clearly identified goals and objectives in place, the effectiveness of these clinical ethics services in meeting organisational goals and objectives is difficult to ascertain. In phase 2, the relation between effectiveness and accountability structures will be explored from the perspectives of a number of key stakeholders.…”
Section: Accountabilitymentioning
confidence: 99%